2021
DOI: 10.1080/17439760.2021.1926532
|View full text |Cite
|
Sign up to set email alerts
|

What are character strengths good for? A daily diary study on character strengths enactment

Abstract: While character strengths are expected to contribute to the 'good life,' they also may serve specific purposes (e.g., the strength of curiosity should support the acquisition and use of knowledge). This study explored the potential functions of character strengths from a within-person perspective. We used a literature review and qualitative and quantitative surveys to determine potential functions. This resulted in 17 distinguishable functions (e.g., 'feeling free and independent'). We used a diary study that … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…From a broader perspective, recent studies have shown that specific character strengths, foremost kindness, teamwork, and love, but also curiosity, honesty, zest, social intelligence, fairness, leadership, gratitude, hope, and humor, have strong associations with the social facet of wellbeing in adults, (i.e., positive relationships with others; Wagner et al, 2020). Moreover, another study found that when an individual displays the character strengths of love, kindness, social intelligence, and honesty in everyday life, they tend to experience higher levels of loving interactions with others (Gander et al, 2021). Also, specific character strengths including love, teamwork, and leadership have been found to be displayed more frequently in close personal relationships, (i.e., between family and friends Wagner et al, 2021), while close relationships with others increase the likelihood of positive consequences of strengths-related behavior (Lavy et al, 2014).…”
Section: Character Strengths and Positive Friendshipsmentioning
confidence: 99%
“…From a broader perspective, recent studies have shown that specific character strengths, foremost kindness, teamwork, and love, but also curiosity, honesty, zest, social intelligence, fairness, leadership, gratitude, hope, and humor, have strong associations with the social facet of wellbeing in adults, (i.e., positive relationships with others; Wagner et al, 2020). Moreover, another study found that when an individual displays the character strengths of love, kindness, social intelligence, and honesty in everyday life, they tend to experience higher levels of loving interactions with others (Gander et al, 2021). Also, specific character strengths including love, teamwork, and leadership have been found to be displayed more frequently in close personal relationships, (i.e., between family and friends Wagner et al, 2021), while close relationships with others increase the likelihood of positive consequences of strengths-related behavior (Lavy et al, 2014).…”
Section: Character Strengths and Positive Friendshipsmentioning
confidence: 99%
“…VanderWeele’s argument that virtue is a crucial component of flourishing has been supported by an increasing number of studies linking character strengths to subjective well-being, healthy social relationships, success in academic and occupational settings, and healthy lifestyle behaviors [ 83 , 84 , 85 ]. Briefly, character strengths are positively valued personality traits that, while generally stable over time and context, can be influenced by specific cultural values, instruction, and interventions [ 86 , 87 ].…”
Section: Consideration Of Human Virtues Character Strengths and Socia...mentioning
confidence: 99%
“…To measure daily character strengths the Character Strengths State Rating Form (CSSRF; Gander et al, 2021) was used. We adapted the answer scale from a 7-point to 11-point scale from 0 ("never") to 10 ("always") in order to unify the answer scales of all daily items.…”
Section: Instrumentsmentioning
confidence: 99%